Komunikasi Simbolik Masyarakat Sunda dalam Pemaknaan Situs Danau Bandung Purba - Shofyan Hikmal Rusdyansyah; Ahmad Taufiq Maulana Ramdan; Ridma Meltareza (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
This study aims to analyze how the public constructs meanings of the Ancient Bandung Lake sites through Herbert Blumer’s Symbolic Interactionism perspective. This study employs a qualitative approach with a case study method to examine the process of meaning construction within the Sundanese community. Data were collected through observation, in-depth interviews, and literature review, and were analyzed using descriptive qualitative analysis. The findings reveal that the community perceives Gunung Batu Lembang, Pawon Cave, and Sanghyang Tikoro not merely as geological sites, but also as symbols of history, cultural identity, and collective memory. These meanings encourage the community to preserve cultural values and transmit them across generations. Furthermore, the meanings are continuously constructed and modified through social interaction, scientific knowledge, and changing social contexts. The study concludes that the meanings attached to the Ancient Bandung Lake sites are socially constructed through symbolic interaction. Therefore, the findings contribute to a broader understanding of how cultural communication and symbolic interaction shape the preservation of cultural identity through the meanings attached to heritage sites.